Multi-criteria decision-making analysis for hospital selection in the telemedicine environment - Albahrey, Osamah Shihab Ahmed (Tanjong Malim, 2019)
Multi-criteria decision-making analysis for hospital selection in the telemedicine environment by Albahrey, Osamah Shihab Ahmed